Lima and the changing conditions of ethnicity - Bonilla Mayta, Heraclio (2018)
This essay gives an account of the significant changes that Lima capital has undergone since its foundation and with greater importance since the second half of the 20th century. The impact caused by migrations from the interior of the country to the capital is reflected not only demographically but also in the ethnic aspect. The process of adaptation of both parties, both residents of Lima and migrants have become new cultural elements such as family styles, life, speech, etc